2010
DOI: 10.1007/s11703-010-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on soluble protein content and protective enzyme system in cotton leaves

Abstract: The effects of soil drought on soluble protein content and protective enzyme system of cotton leaves at different positions were studied in the transgenic cotton cultivar, Lumianyan28. The results indicated that the soluble protein content in main stem leaves and in middlefruit branch leaves under drought treatment were higher than that of CK, the normal soil water management treatment. Lower fruit branch leaves under drought treatment had higher protein and enzyme levels than CK treatments. From June 25 to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…Stress adaptability reveals constitutively enhanced levels of several stress-related proteins subsequently associated with soluble protein. Hence, the soluble protein and cellular protection enzymes increase under abiotic stress [21,24]. Our study exhibited a similar pattern of hike in the total soluble protein content with an increase in Al-mediated stress.…”
Section: Discussionsupporting
confidence: 74%
“…Stress adaptability reveals constitutively enhanced levels of several stress-related proteins subsequently associated with soluble protein. Hence, the soluble protein and cellular protection enzymes increase under abiotic stress [21,24]. Our study exhibited a similar pattern of hike in the total soluble protein content with an increase in Al-mediated stress.…”
Section: Discussionsupporting
confidence: 74%
“…These results are in consistent with the result of NPQ, which indicate that with the increase of drought stress, the PSII reaction center was damaged by ROS. Several studies have reported on the association between the activity of the antioxidant enzyme system and drought tolerance in plants but with variable and inconsistent results (Li et al, 2010. This variation may be caused by the activity of the antioxidant enzyme system and antioxidant concentration, among many other factors.…”
Section: Discussionmentioning
confidence: 99%
“…The high content of soluble protein can help maintain a relatively low y S in plant cells and further alleviate damages that result from salt stress (Du et al, 2007). Exogenous Spd treatment could help produce new induced proteins and/or accelerate the synthesis process of some original proteins and, thus, adjust y S of cells to keep a certain turgor and further to ensure the normal proceeding of a series of physiological and biochemical processes under stress conditions (Li et al, 2010b). Salt stress is also known to affect the free amino acid contents in plants (Surabhi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%